TO STUDY THE EFFECT OF TADALAFIL IN IMPROVING URODYNAMIC PARAMETERS IN SPINAL CORD INJURY PATIENTS: A RANDOMIZED CONTROLLED TRIAL - KARMENDRA SINGH KUSHWAHA; OM PRAKASH; NIKHIL AGARWAL; PRERNA BHASKAR (Asian Journal of Pharmaceutical and Clinical Research, 2024)
Objectives: The aim of the study was to compare the effect of single dose Tadalafil 20 mg 2 h after administration on Urodynamic study (UDS) parameters and comparison with calcium+vit-D3 (control) in spinal cord injury (SCI). Methods: Sixty-six SCI individuals with lower urinary tract symptoms (LUTS) and upper motor neuron bladder were randomized into Tadalafil group (n=33) and calcium+vitD3 group (n=33). UDS was done and parameters (maximum detrusor filling pressure [MDFP], maximum bladder capacity, and bladder compliance) were recorded at baseline and 2 h after administration of respective drugs in both groups and comparison was done. Results: Statistically significant improvement in mean MDFP from 24.42±6.75 to 21.12±5.72 cm H2O (p < 0.001), mean maximum bladder capacity from 263.94±108.48 to 287.67±112.71 mL (p<0.001), and mean bladder compliance from 11.07±4.31 to 13.94±5.13 mL/cm H2O (p<0.001) was observed in Tadalafil group whereas in calcium+vit-D3 group, no significant improvement was observed. When we compared difference of mean of MDFP, bladder capacity, and bladder compliance between Tadalafil and calcium+vitD3 group, significant improvement (p<0.001) in Tadalafil group was noted as compared to calcium+vitD3 group. Conclusions: Single dose of oral Tadalafil 20 mg has shown significant improvement in MDFP, bladder capacity, and bladder compliance in SCI individuals with LUTS as compared to control.